Aspects of the prevention of light damage during drying and rehydration of the desiccation-tolerant grass Eragrostis nindensis - Bergh, Nicola G (Department of Biological Sciences, 2017)
There are two main mechanisms of desiccation-tolerance in angiosperms. Both of these (poikilochlorophylly and homoiochlorophylly) involve adaptations to prevent light-induced damage as the plants dry and rehydrate. The poikiolchlorophyllous grass E. nindensis was investigated to determine physiological responses to light during drying, and mechanisms of tolerance of dehydration. The desiccation-sensitive E. curvula was investigated simultaneously as a control in order to compare responses of tolerant and sensitive relatives. Quantum efficiency of photosystem II was determined using chlorophyll fluorescence parameters and levels of photosynthetic pigments (chlorophylls and carotenoids) and of anthocyanins were measured. Electrolyte leakage of drying and rehydrating leaves was monitored to determine the extent of damage to membranes. Quantum efficiency and photosynthetic pigment contents were reduced in both plant§ dehydrated to <2% RWC; only E. nindensis recovered to initial levels. Both plants accumulated anthocyanins but these reached greater levels in E. nindensis and were found on the entire length of the leaf. On rehydration, E. nindensis lost the anthocyanins as it reconstituted chlorophylls. Neither species showed marked increases in electrolyte leakage but E. curvula did not recover on rewatering.